Faktor-Faktor yang Merefleksikan Family Business Brand dalam Perspektif Generasi Penerus Perusahaan Keluarga Pada Family Business Community Universitas Ciputra - Annisa Aisyah Fayola; Metta Padmalia; Junko Alessandro Effendy (Management and Sustainable Development Journal, 2021)
This research in done to find out the factors that can reflect family business brand in the perspective of family business next generation. Research data collection is distributed as many as 135 respondents to the next generation of family companies that join seventh, eight, and ninth batch of Universitas Ciputra in which majority are those who have involved in family business. Sampling is done with non-probability sampling technique method and purposive sampling method. Data analysis method that is used Partial Least Square Structural Equation Modeling (SEM PLS) with the help of smartPLS 3.0 program. The results of the analysis in this research indicate that Family Business Brand can be reflected by the factors of Family Firm Identity, Family Firm Image, and Family Firm Reputation. Family Firm Identity factors consist of family influence, family goal value, company origin, name of family business / company, and overlapping family business value. The Family Firm Image factors consist of the description of family agreement, the channel or channel that is used, the behavior of members that reflect values, and the history of family business sacrifice. Family Firm Reputation factors consist of the company's leadership vision, workplace environment, and company financial performance. The results of data process show that the factors that reflect the Family Business Brand in the perspective of next generation are if it is sorted from the highest that is, family firm identity factor, family firm image factor, and family firm reputation factor. Key words: family business brand, family firm identity, family firm image, family firm reputation, next generation, family business